PSI-35 Foot and hair shedding scores of crossbred cattle grazing native rangeland differ by age group. (30th November 2020) - Eiguren, Nick M; Peterson, Katie; McFarlane, Zach D
Abstract: Structural soundness is crucial to improve productivity and longevity of beef cattle in rangeland landscapes. In addition, hair shedding scores are utilized to select for heat tolerant cattle. Thus, the objective of this study was to collect data indicative of cattle adaptability to extensive rangeland landscapes in the Cal Poly beef cattle herd. Three trained technicians assigned claw set, foot angle and hair shedding scores. All data were collected over a 2-day period (n = 3 ranch locations) and foot scores were only collected from females (n = 211) that were at least 1 year of age. Each female was assigned a score for foot angle and claw set (1–9, 5 being ideal). A hair shedding score was also allocated (1–5, 1 = 0% winter coat, 5 = 100% winter coat) to both cows and calves of dams assigned to different age groups. Cattle were retrospectively assigned to a group based on age (Young = 2–3 years of age, Moderate = 4–7 years of age, Old = 8+ years of age) and data were analyzed with the main effects of ranch location and cow age group. Ranch location had no impact (P > 0.05) on foot score or hair shedding score. Cow age group had a significant impact (P < 0.01) on claw set, with young cows exhibiting a lower and more ideal foot score. However, cow age had no effect on hoof angle (P = 0.23). Young cows had a greater (P < 0.001) hair shedding score than their counterparts. Calf hair shedding score was not different (P ≥ 0.23) among dam age groups or ranch locations. Thus, these data indicate that feet and leg structure is compromised as cows age, and younger cows with higher hair shedding scores may lack adaptability to heat stress.